Bihar Fourth Five Year Plan Progress Report for the Period Ending March, 1967 - Planning Commission (Planning Commission, 1967)
Agricultural Programme Co-operation Community Development and Gram Panchayat Irrigation and Flood Control Industries and Mining Transport and Communications Social Services, Miscellaneous.
Bihar